New Lupanes from Alstonia scholaris Reducing Uric Acid Level - Hu, Bin-Yuan; Zhao, Yun-Li; Xu, Yuan; Wang, Xiao-Na; Luo, Xiao-Dong (Planta Medica, 2023)
Twelve lupanes including three new compounds named alstoscholarilups A−C (1–3) were isolated from the leaves of Alstonia scholaris. Their structures were elucidated by spectroscopic analysis and ECD calculation. Structurally, compound 1 with a rare A ring-seco skeleton formed lactone and degraded C-3, while 2 with a 28-nor and 3 with a 29-nor-lupane skeleton supported the phytochemical diversity and novelty of the plant. Pharmacologically, compounds 4, 7, and 10 reduced the serum uric acid (UA) levels of mice significantly.
Keywords: Alstonia scholaris; Apocynaceae; reducing UA levels; lupanes